Korenine škofa Slomška po materini strani - Golec, Boris (Časopis za zgodovino in narodopisje, 2022)
This article discusses the maternal ancestors of the Bishop of Lavant, Blessed Anton Martin Slomšek (born 1800, died 1862), about which very little has been known so far. Slomšek’s mother, Marija Zorko (born 1779, died 1816), was born in humble circumstances in the parish of Črešnjice near Frankolovo in the village of Brdce, where her father Gregor Zorko had married a much older widow, Agata Pintar, and went to live with her in her cottage. The surname Zorko is documented as early as 1527 in the village of Kamna Gora, where Gregor was originally from. However, due to poorly preserved sources, it is only possible to trace the family continuously from the end of the 17th century onwards. Finally, the most probable origin of Gregor’s wife Agata has been traced. It seems that the couple married in the neighbouring parish of Dramlje, then still part of the parish of Ponikva, where Bishop Slomšek was born. Agata was born in the village of Straža na Gori in the cottager’s family Graben or Grabenšek.
Keywords: biografije; rodoslovje; Slomšek (rodbina); Slomšek, Anton Martin; slovenski škofi; zgodovina; Zorko (rodbina)